According to our hearts : Rhinelander v. Rhinelander and the law of the multiracial family - Onwuachi-Willig, Angela (Yale University Press, 2013)
'According to Our Hearts' looks at what it means to be a multiracial couple in the United States today. It begins with a look back at a 1925 case in which a two-month marriage ends with a man suing his wife for misrepresentation of her race, and shows how our society has yet to come to terms with interracial marriage. Angela Onwuachi-Willig examines the issue by drawing from a variety of sources, including her own experiences.